Descriptive Anatomy of the Porcine Ventral Abdominal Wall as a Basis for Training Ventral Hernia Repair Techniques - Maaike Vierstraete; Nicky Van Der Vekens; Roel Beckers; Yohann Renard; Filip Muysoms (Journal of Abdominal Wall Surgery, 2024)
Background: In recent times there has been a surge in innovative techniques concerning complex abdominal wall surgery. The availability of simulation models for comprehensive training and skill set development remains limited.Methods: Cadaveric dissections of the porcine abdominal wall were conducted to assess the suitability of anesthetized porcine models for training in both minimally invasive and open surgical procedures.Results: The panniculus carnosus, a typical muscular layer in mammals, is the outermost layer covering the anterolateral abdominal wall. Beneath it, there are four main pairs of abdominal wall muscles, mirroring the human anatomy. The rectus abdominis muscle runs straight along the linea alba and is surrounded by the rectus sheath, which is formed by the fusion of the lateral abdominal wall muscles and differs along the different regions of abdominal wall. The orientation of the muscle fibers in the lateral abdominal wall muscles, i.e., musculus obliquus externus, internus and transversus, is comparable to human anatomy. Although the transition lines between their muscular and aponeurotic part differ to some extent. Relevant for the adoption of surgical techniques, the transversus abdominis muscle is well-developed and resembles a bell curve shape as it transitions from its muscular to aponeurotic part.Conclusion: Despite minor differences in abdominal wall anatomy between pigs and humans, the porcine model provides a high level of fidelity in terms of both anatomical features and the development of skill sets relevant to hernia surgery.